Phylogeny, Global Biogeography and Pleomorphism of Zanclospora - Réblová, Martina; Kolařík, Miroslav; Nekvindová, Jana; Miller, Andrew N; Hernández-Restrepo, Margarita (Microorganisms, 2021)
Zanclospora (Chaetosphaeriaceae) is a neglected, phialidic dematiaceous hyphomycete with striking phenotypic heterogeneity among its species. Little is known about its global biogeography due to its extreme scarcity and lack of records verified by molecular data. Phylogenetic analyses of six nuclear loci, supported by phenotypic data, revealed Zanclospora as highly polyphyletic, with species distributed among three distantly related lineages in Sordariomycetes. Zanclospora is a pleomorphic genus with multiple anamorphic stages, of which phaeostalagmus-like and stanjehughesia-like are newly discovered. The associated teleomorphs were previously classified in Chaetosphaeria. The generic concept is emended, and 17 species are accepted, 12 of which have been verified with DNA sequence data. Zanclospora thrives on decaying plant matter, but it also occurs in soil or as root endophytes. Its global diversity is inferred from metabarcoding data and published records based on field observations. Phylogenies of the environmental ITS1 and ITS2 sequences derived from soil, dead wood and root samples revealed seven and 15 phylotypes. The field records verified by DNA data indicate two main diversity centres in Australasia and Caribbean/Central America. In addition, environmental ITS data have shown that Southeast Asia represents a third hotspot of Zanclospora diversity. Our data confirm that Zanclospora is a rare genus.
Keywords: geographic distribution; life cycle; GlobalFungi; conidiogenesis; taxonomic novelties; new typification; molecular systematics; Chaetosphaeriales